Physiological Responses to Treadmill and Cycle Exercise - Abrantes, C.; Sampaio, J.; Reis, V.; Sousa, N.; Duarte, J. (International Journal of Sports Medicine, 2012)
This study aimed to identify differences in the acute cardio-respiratory, metabolic and perceptual responses between exercise performed on the treadmill and on the cycle ergometer at several intensities. The sample comprised of 20 voluntary male participants (age=22.5±1.8 years; height=177.7±7.0 cm; body mass=72.6±7.9 kg; fat mass=7.87±1.3%) that performed 5 submaximal 8 min exercise bouts, interspersed with a 10 min period of passive recovery. Exercise intensity used on the treadmill was 10, 12, 14, 15 and 16 km/h (0% gradient), and 80, 120, 160, 180 and 200 W on the cycle ergometer (65–70 rpm). There was a significant mode effect and also mode×intensity interaction in oxygen uptake and heart rate with higher values in the treadmill protocol (F=32.0 p=0.000, η2=0.65 and F=132.0 p=0.000, η2=0.88, respectively). The respiratory exchange ratio and blood lactate concentrations were not different across modes (F1, 18=1.9 p=0.183 and F1, 17=0.1 p=0.964, respectively) and rate of perceived exertion values were higher in the cycle ergometer (F1, 12=1.2 p=0.288). Generally, results showed a larger exercise mode effect on the cardio-respiratory variables with higher response patterns on the treadmill, differing according to exercise intensity.
Keywords: exercise mode; cardiorespiratory; metabolic; perceptual; ergometers